Bcl-2 antagonizes apoptotic cell death induced by two new ceramide analogues - Wieder, Thomas; Geilen, Christoph C; Kolter, Thomas; Sadeghlar, Farsaneh; Sandhoff, Konrad; Brossmer, Reinhard; Ihrig, Petra; Perry, David; Orfanos, Constantin E; Hannun, Yusuf A (FEBS letters, 1997)
Ceramides which arise in part from the breakdown of sphingomyelin comprise a class of antiproliferative lipids and have been implicated in the regulation of programmed cell death better known as apoptosis. In the present study, two new synthetic ceramide analogues, N-thioacetylsphingosine and FS-5, were used in Molt4 cells to induce cell death. Besides their cytotoxic effects at concentrations ≥14 μM the data obtained clearly show that both analogues induced apoptosis at concentrations below this critical concentration as assessed by trypan blue exclusion and cleavage of the death substrate poly-(ADP-ribose) polymerase (PARP). Additional experiments in bcl-2-transfected Molt4 cells revealed that the apoptotic but not the lytic effects of the analogues were antagonized by the apoptosis inhibitor Bcl-2. Furthermore, neither N-thio-acetylsphingosine nor FS-5 induced PARP cleavage in bcl-2-transfected Molt4 cells indicating that the induction of apoptotic cell death by cell permeable ceramides is not due to unspecific disturbance of the cell membrane.